Cyber crime in times of covid-19: violation of constitutional rights? - Núñez Pérez, Fernando Vicente (2020)
The use of the Internet developed a new form of illegal configuration, known as Cybercrime. In this sense, international and national instruments have been developed to avoid impunity, seeking to punish such conduct. The context of COVID-19 shows us - much more - that our activities depend on technological support, which generates new forms of Cybercrime